Fairies, Lovers, and Glass Palaces: French Influences on Thirteenth-Century Hebrew Poetry in Spain—the Case of Ya'akov ben El'azar's Ninth Maḥberet - Bibring, Tovi (The Jewish quarterly review, 2017)
This article provides an intertextual reading of "The Love of Sahar and Kima," the ninth mahberet of Y'akov ben Elazar's Sefer ha-meshalim. This tale highlights the contrast between physical and spiritual love, feudal and religious constraints, and "courtly" ideas and a parody of those ideas. The paper expands upon the current knowledge of the thematic, structural, and ideological parallels between Y'akov ben Elazar's work and the literature of medieval France, and presents a number of prominent and specific examples that indicate the influence of the Matière de Bretagne on this mahberet. Simultaneously, the paper identifies Ya'kov ben Ela'zar as an original European writer who made use of existing literary models, but who was independent in his muse and inspiration. The originality of this paper lies in the fact that for the first time in scholarly research, it is proven that there are vestiges of the fairy tale in Sefer ha-meshalim, and that this mahberet can be read as a rationalized fairy tale like those in French literature.